The Effects of Nursing Care and Treatment Algorithm developed for Patients with COVID-19 on Patient Satisfaction - Erdost, Şerife Kartal; Demiröz, Anıl; Arı, Arzu; Karadede, Özkan; Kartoğlu Gürler, Sevdan; Yalçın, Can Ege; Çınar, Fatih; Gemicioğlu, Bilun; Çetinkale, Oğuz; Dirican, Ahmet (Cerrahpaşa Medical Journal, 2025)
Objective: The aim of this study was to determine the benefits of a newly created medical history form, care form, and treatment algorithm protocol designed according to the physiological and psychosocial needs of coronavirus disease-2019 (COVID-19) diagnosed patients. Methods: This was a prospective cross-sectional real-life study conducted in COVID-19 wards of a tertiary health center. Of the 972 patients hospitalized during the study period, 236 patients met the research crite ria, with 124 patients in the control group and 111 patients in the study group. A visual analog scale (VAS) was used to evaluate the nursing care. Results: Of the patients in Group A, 40.0% rated their care as 10, 11.9% as 9, 8.9% as 8, and 1.5% as 7. In Group B, 74.3% rated their care as 10, 15.8% as 9, 5.0% as 8, and 1.0% as 5. There was a significant increase in nurse satisfaction levels and hospitalization duration in Group B (P = .034, P = .008). Conclusion: The algorithm and care form developed in this study are believed to be a guide for nurses work ing in clinics who are inexperienced in caring for patients with COVID-19, increasing patient satisfaction and contributing to care quality. Cite this article as: Erdost ŞK, Demiröz A, Arı A, et al. The effects of nursing care and treatment algorithm developed for patients with COVID-19 COVID-19 on patient satisfaction. Cerrahpaşa Med J. 2025, 49, 0014, doi:10.5152/cjm.2025.25014.